2020
DOI: 10.3389/fvets.2019.00509
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanotrap Particles Preserve the Stability of Venezuelan Equine Encephalitis Virus in Blood for Laboratory Detection

Abstract: Most of the modern techniques used for identification of viral-induced disease are based on identification of viral antigens and/or nucleic acids in patient's blood. Diagnosis in the field or in remote locations can be challenging and alternatively samples are shipped to diagnostic labs for testing. Shipments must occur under controlled temperature conditions to prevent loss of sample integrity. We have tested the ability of magnetic Nanotrap ® (NT) particles to improve stability and detection of Venezuelan eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…Nanotrap particles capture and concentrate live SARS-CoV-2 from transport medium. In previous studies, we have shown that our hydrogel particles (Nanotrap particles) functionalized with high-affinity chemical baits capture and concentrate a variety of respiratory viruses from biological samples, including Influenza A and B, RSV, and Coronavirus 229-E [11][12][13][14] . In light of this, we asked whether the same particles could capture and concentrate SARS-CoV-2 from transport medium in order to improve diagnostic testing for In all experiments, a simple four-step workflow was used to capture and concentrate the virus using our Nanotrap particles.…”
Section: Resultsmentioning
confidence: 99%
“…Nanotrap particles capture and concentrate live SARS-CoV-2 from transport medium. In previous studies, we have shown that our hydrogel particles (Nanotrap particles) functionalized with high-affinity chemical baits capture and concentrate a variety of respiratory viruses from biological samples, including Influenza A and B, RSV, and Coronavirus 229-E [11][12][13][14] . In light of this, we asked whether the same particles could capture and concentrate SARS-CoV-2 from transport medium in order to improve diagnostic testing for In all experiments, a simple four-step workflow was used to capture and concentrate the virus using our Nanotrap particles.…”
Section: Resultsmentioning
confidence: 99%
“…Also, as we have previously demonstrated that the Nanotrap particles used in this study can also capture and concentrate influenza viruses, RSV, and other coronaviruses 13 , we are confident that the method described here will be compatible with the respiratory virus panel tests that are under development. Moreover, while we did not address assays for viral antigens, next generation sequencing assays, or antibody assays in this work, Nanotrap particles can be used to improve those testing modalities 10,11,[24][25][26] and we look forward to expanding our work into that area. Nanotrap particles are pelleted with a magnet, the supernatant is removed, and the particle pellet is resuspended in a viral lysis solution.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown that hydrogel particles functionalized with high-affinity chemical baits are able to capture and concentrate from biological samples a variety of respiratory viruses, including Influenza A and B, RSV, and Coronavirus 229-E [10][11][12][13] . In light of this, we asked whether the same particles could capture and concentrate SARS-CoV-2 from transport medium and saliva in order to improve diagnostic testing for COVID -19. In all experiments, a simple four-step workflow was used to capture and concentrate the virus using hydrogel particles made by Ceres Nanosciences (Nanotrap particles).…”
Section: Nanotrap ® Particles Capture and Concentrate Inactivated Sarmentioning
confidence: 99%
“…Nanotrap particles have enhanced the detection sensitivity and specificity by allowing enrichment of the sample through molecular size sieving. Recently, magnetic nanotrap particles were found to concentrate and preserve the stability of VEEV and its proteins in whole human blood at elevated temperature (40°C) and prolonged storage conditions (72 h) [330]. Recently, magnetic nanotrap particles with different affinity baits consisting of Cibacron Blue, acrylic acid, and Reactive Red 120 have been explored to trap and enrich ZIKV, DENV, and CHIKV in human urine and saliva spiked with 1 × 10 6 PFU/mL of virus and found that a nanotrap system with Reactive Red 120 as the aromatic bait could recover 8-16-fold higher genomic copies of ZIKV, CHIKV, and DENV.…”
Section: Nanotrapsmentioning
confidence: 99%